Applied behavior analysis for teachers - Alberto, P.A.; Troutman, A.C. (Boston : Pearson, 2013)
The market-leading book Applied Behavior Analysis for Teachers gives you what you need to understand to use the principles and practices of applied behavior analysis in the classroom. The content is presented clearly, in a friendly, accessible--even fun--manner. The ninth edition uses classroom-based examples and practices firmly grounded in research. Content is presented in the order of decision-making by a teacher who has a student exhibiting challenging behavior in class or a student who needs to execute a behavior-change project. The text covers identifying target behavior, collecting and graphing data, functional assessment, experimental design, arranging antecedents and consequences, and generalizing behavior change. The importance of ethical considerations in using applied behavior analysis in the classroom is now presented at the beginning of the book to highlight the importance of applying principles and practices responsibly.
Includes index and reference.
Keywords: Behavior modification; Students -- Psychology; Human behavior